2005
DOI: 10.1111/j.1439-0485.2005.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and gonad production of the sea urchin Hemicentrotus pulcherrimus in the fucoid bed and algal turf in northern Japan

Abstract: To clarify the differences in the growth and gonad size of the sea urchin Hemicentrotus pulcherrimus among algal sere, the study was conducted in June and July, and September 1998 at three fucoid beds in Oga and at three algal turfs in Hachimori, Akita Prefecture in northern Japan. The most rapid growth was observed in a large perennial fucoid bed at the climax stage. Growth in a small perennial Chondrus ocellatus‐dominated bed in algal turfs in the seral stage was then high. The slowest growth was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
(21 reference statements)
2
11
0
Order By: Relevance
“…Endo et al (2007) studied the vertical distribution and food of M. nudus and H. pulcherrimus in fucoid beds and concluded that foods such as sessile animals ensure the gonad development of M. nudus in coralline flats, eliminating the migration of the sea urchin to fucoid beds in shallow waters. Seasonal maximum gonad indices of H. pulcherrimus in coralline flats and fucoid beds were 11, markedly lower than those in fucoid beds at other localities (Agatsuma and Nakata 2004;Agatsuma et al 2005a). This suggests that H. pulcherrimus ingest the dominant foods.…”
Section: -1 Seasonal Migrationmentioning
confidence: 89%
See 3 more Smart Citations
“…Endo et al (2007) studied the vertical distribution and food of M. nudus and H. pulcherrimus in fucoid beds and concluded that foods such as sessile animals ensure the gonad development of M. nudus in coralline flats, eliminating the migration of the sea urchin to fucoid beds in shallow waters. Seasonal maximum gonad indices of H. pulcherrimus in coralline flats and fucoid beds were 11, markedly lower than those in fucoid beds at other localities (Agatsuma and Nakata 2004;Agatsuma et al 2005a). This suggests that H. pulcherrimus ingest the dominant foods.…”
Section: -1 Seasonal Migrationmentioning
confidence: 89%
“…For H. pulcherrimus, the seasonally maximum gonad index were more than 20 in Sargassum bed (Agatsuma and Nakata 2004), and the kelp bed dominated by Undaria pinnatifida and Saccharina japonica (Ogasawara et al 2011), 18.5 in Acrosorium polyneurum bed (Agatsuma et al 2006b), 18 in E. bicyclis bed (Agasuma et al 2012) and 10-11 in barrens (Agatsuma et al 2006b;Endo et al 2007). By contrast, in the fucoid beds dominated by the large fucoids Myagropsis myagroides, Sargassum piluliferum and Sargassum patens, the maximum gonad index was 9.8, which is markedly low (Endo et al 2007).…”
Section: -1a Gonad Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Pearse 1980, Meidel & Scheibling 1998, Agatsuma et al 2005a. The most rapid growth and highest gonad production are found in laminarian beds, followed by algal turf, consisting mainly of red algae such as Chondrus ocellatus.…”
Section: Introductionmentioning
confidence: 99%